Development of a quantitative evaluation tool for Seoul's community-based participatory health program 'building healthy communities'. (23rd June 2022) - Song, Sunmi; Kim, Hae-Young; Heo, Hyun-Hee
Summary: Community-based participatory health (CBPH) programs are important for addressing health disparities; however, the limited development of validated scales to measure outcomes may hinder the utilization and upscaling of such programs. Thus, this study aimed to develop a culturally appropriate and valid tool for the quantitative evaluation of a CBPH program and to test theory-driven pathways of associations among participation, social capital, empowerment and health outcomes. This study used a participatory and mixed methods approach. Formative research, including a literature review, survey results over the past 2 years, focus group interviews and participatory evaluation committee meetings, was conducted. Four program components—participation, social capital, empowerment and quality of life (QoL)—were identified and used to construct a validated evaluation tool. A total of 317 participants (89.9% women, mean age = 57.7 ± 11.5 years) responded to the survey. The data were analyzed for internal consistency and factor structure. Structural equation modeling (SEM) was used to test the theoretical pathways of health promotion through the CBPH program. The SEM results showed two significant mediation pathways such that participation in interventions was associated with higher QoL via social capital accumulation and improved empowerment. Our results exemplify a validated scale that can be used to evaluate the intermediate- and long-term outcomes of a CBPH program. Lay Summary: This study aimed to develop a reliable and valid tool for the evaluation of community-based participatory health (CBPH) programs and to test a pathway to explain how participation may be associated with better health. The study used mixed methods, including focus group interviews, analysis of survey data from the past 2 years, participatory evaluation committee meetings and a main survey. Four core program components were identified: participation, social capital, empowerment and quality of life. In total, 317 participants responded to the survey. The results also showed that program participation was associated with a higher quality of life through increased social capital and empowerment. In conclusion, the developed evaluation tool can be used to evaluate the intermediate-and long-term outcomes of a CBPH program.